2023
DOI: 10.1111/cgf.14765
|View full text |Cite
|
Sign up to set email alerts
|

In‐the‐wild Material Appearance Editing using Perceptual Attributes

Abstract: Figure 1: Our approach enables intuitive appearance editing of high-level perceptual attributes. Our framework takes as an input a single image of an object (top) and produces high-quality edits of material attributes such as glossy or metallic, while preserving the geometrical structure and details (bottom). The"+" and "-" indicate whether the target high-level perceptual attribute is increased or decreased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Discussion While other algorithms for dimensionality reduction exist (e.g., multidimensional scaling or kernel principal component analysis) we chose the IsoMap algorithm since it works well with arbitrary distance matrices and handles well non‐linear spaces [TdL00]. Other alternatives using neural networks, following previous works on perceptual spaces for material appearance [LMS*19; DLC*22; SL23], were considered, but we found that IsoMap works well in our case, and produces stable and meaningful manifolds that can be easily navigated, while the latent spaces of neural‐based methods might lead to unintuitive spaces and would require re‐training with extensive labeled data for translucent appearance.…”
Section: A Perceptually Meaningful Space For Translucent Appearancementioning
confidence: 99%
“…Discussion While other algorithms for dimensionality reduction exist (e.g., multidimensional scaling or kernel principal component analysis) we chose the IsoMap algorithm since it works well with arbitrary distance matrices and handles well non‐linear spaces [TdL00]. Other alternatives using neural networks, following previous works on perceptual spaces for material appearance [LMS*19; DLC*22; SL23], were considered, but we found that IsoMap works well in our case, and produces stable and meaningful manifolds that can be easily navigated, while the latent spaces of neural‐based methods might lead to unintuitive spaces and would require re‐training with extensive labeled data for translucent appearance.…”
Section: A Perceptually Meaningful Space For Translucent Appearancementioning
confidence: 99%